Dual-Polarized On-Chip Antenna for 300 GHz Full-Duplex Communication System - Linyan Guo; Ming Deng; Qisheng Zhang; Xinyue Zhang; Zhenzhong Yuan (International Journal of Antennas and Propagation)
This paper presents a novel design of compact orthogonally polarized on-chip antenna to realize 300 GHz full-duplex communication system with high isolation. It consists of a dipole antenna for horizontal polarization and a disk-loaded monopole antenna for vertical polarization. They are in good cross-polarization state with more than 90 dB of self-interference suppression and then can be used to achieve good isolation between transmitting and receiving antennas. In addition, two dual-polarized antennas have been adopted in two separated transceivers to study their isolation performance. Furthermore, this compact antenna only occupies an active area of 390 μm × 300 μm × 78 μm and can be used for multiple-input multiple-output application as well.